REVIEW OF ELECTRONIC LAND CERTIFICATES IN PROVIDING LEGAL CERTAINTY AND PROTECTION IN KUDUS REGENCY - Wardhani, Lidya Christina; Alodia Dwi Hartanto, Ivana (Jurnal Meta-Yuridis, 2025)
The land registration activity produces land certificates as proof of land ownership rights, issued physically in the form of a book. There are several potential abuses related to land certificates, including forgery, duplication, overlapping ownership claims, and instances of lost or damaged certificates. To facilitate services to the community and to provide legal certainty and protection, the conversion of land certificates into electronic land certificates is carried out by the government, including by the Kudus Regency Government. The approach method used in this paper is a sociological-juridical approach.The research findings indicate that Kudus Regency, through the Kudus Regency Land Office, is striving to realize the Complete Regency/City Program by implementing electronic certificates. The implementation of electronic land certificates in Kudus Regency shows that the digitization of the land registration system can improve service efficiency, reduce bureaucracy, and close gaps in illegal brokering practices that harm the community. The support provided by the Kudus District Land Office includes socialization, training, and the application of encryption technology, which strengthens public trust in the digital land system. Keywords: Electronic Land Certificates, Legal Certainty, Legal Protection